Judgement without justice: on the efficacy of the European human rights regime. Issue 2 (23rd February 2017) - Guasti, Petra; Siroky, David S.; Stockemer, Daniel
ABSTRACT: The European Court of Human Rights (ECtHR) is widely regarded as the most important human rights court worldwide. This article investigates the extent to which the court addresses cases from countries with the worst human rights performance. Using a new data set on all ECtHR judgments from 1995–2012, the analysis suggests that the ECtHR does not deliver its judgments against members of the Council of Europe with the worst human rights records, but instead against more democratic and affluent states. The reason is that litigating in front of a supranational court requires capacities that vulnerable people are unlikely to possess, except when aided by transnational advocacy groups. However, more judgements are issued against countries that lack independent judiciaries, where cases are less likely to be resolved at the domestic level. While the ECtHR might not address the worst human rights crimes, it plays a subsidiary role in the European human rights protection system by compensating for weak domestic judiciaries. However, the court's inability to independently pursue litigation, together with the lack of capacity in some countries to bring cases forward, have hampered more effective protection of human rights for the most vulnerable in Europe.